Investigation And Evaluation Of Brand Equity From The Perspective Of Employees (Case Study Guilan Regional Electricity Company) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Because in service organizations, employees can influence customers' perceptions and purchasing decisions and ultimately play a key role in the success of the organization, strengthening brand equity based on employees can create a lasting competitive advantage for the organization. The role of human resources in the electricity industry is also fundamental and it is necessary that companies in the electricity industry, understanding the role of employees in promoting this industry, create brand equity based on employees. The purpose of this study is to assess the special value of the Employee-based Brand Equity in Guilan Regional Electricity Company. This research is applied and due to the abnormality of the research data, it has been investigated using SMARTPLS2 structural equation software. The statistical population of the study includes 142 specialized employees working in GREC. 104 of these individuals were selected as a statistical sample by simple random sampling from the statistical population. Finally, the effect of acceptance on Information Generation, and knowledgedissemination; the effect of human factor on acceptance, Information Generation, and knowledge dissemination; the effect of information creation on knowledge dissemination; the effect of knowledge dissemination on role clarity and brand commitment'; the effect of role clarity on EBBE; and the effect of brand commitment on EBBE were examined in GREC and according to the calculated values of t-statistic, the result shows that except the effect of acceptance on knowledge dissemination and the effect of knowledge dissemination on brand commitment other hypotheses are confirmed